Connecting community through film in ITE English - McIntyre, Joanna; Jones, Susan (Routledge, 2016)
This chapter offers a critical exploration of the work of beginning teachers of secondary English at the University of Nottingham, who have been involved, alongside their own pupils, in a series of film-making projects which have taken place annually since 2010. During these projects, beginning teachers are mentored by creative practitioners to support their pupils in the creation of short films about their schools and communities. Pupils are supported to develop films from original screenplay through to final production, and beginning teachers learn about what is involved in managing such projects, from practical media skills through to the potential of creative collaboration with community. Pupils’ teachers and families attend a screening of their completed films at a local arts cinema. These projects engage beginning teachers of English with the creative potential of their subject at a time when it has been increasingly framed according to prescriptive models of literacy as a measurable skill set and when changes to the curriculum have further marginalised non-dominant voices. Through examination of the processes and products of these projects as collaborative constructions of place and identity, we show the significant potential of community-based educational partnership. We also argue for the importance of ITE which remains committed to close engagement with the resources of young people and their communities. We explore the power of this for critical literacy learning in current classrooms and as a means of developing beginning teachers’ critical capacity to respond to challenges in the classrooms of the future.